Reasons for rescuing orphans, destitute, neglected or imperilled children: analysis of the work of the Waifs and Strays Society in the late nineteenth century - Annie Skinner (Scottish Journal of Residential Child Care)
This article examines the early work of The Church of England Incorporated Society for Providing Homes for Waifs and Strays by assessing 6824 applications for children's admission to care in the late nineteenth-century. It is based on an archive study of records kept by the Children's Society in England and Wales between 1882 and 1899. A consistent in-depth analysis of the Waifs and Strays Society's policies in practice over 12 years is provided in parallel with the pressures families experienced during a time of harsh Poor Law policies. The focus identifies reasons why children were received into care from poor families when strong moral and political philosophies underpinned privileged professionals in power and in control of children's destinies. Also examined is how the Waifs and Strays Society's policies are reflected in the applications for care. The research addresses the gaps about the practice of the work of early social workers in the community.